EXPERIENCE OF USING MICROSOFT VIRTUALIZATION IN IT ENVIRONMENT OF UNIVERSITY - V. Timofeev; V.G. Galagan; Y.A. Timoshin; O.V. Yurchenko; V.P. Yarchenko (Kherson State University, 2012)
It is shown that server's Virtualization and consolidation of virtual machines on a few of physical servers increases efficiency of capital investments for University in an equipment with the simultaneous increase of availability of resources, reducing downtimeand and after emergency renewal of virtual servers. Universities are faced with a necessity to consolidate present informative resources and all of necessary network infrastructure, which are often created with the use of licensed facilities and products of opened kodas, on a minimum number of physical servers. The authors carried out the transfer of a few physical servers was executed in a virtual environment, utillizing different facilities of virtualizacii of company Maykrosoft, that defined, except for obvious advantages, and a number of limitations with which it is possible to clash in the process of such transfer of the applied servers. We consider free virtualization tools - Virtual PC 2007, Windows 7 - XP Mode, Virtual Server 2005, Hyper-V Server 2008R2, and paid virtualization tool - Windows Server 2008R2 with role Hyper-V installed.